A preliminary study examining terminology used by individuals with lived experience describing beliefs about being targeted or harmed by others. (May 2023) - Buck, Benjamin; Wingerson, Mary; Chander, Ayesha; Tauscher, Justin S.
Highlights: - Individuals with lived experience of persecutory ideation use a variety of terms to describe their experience. - Most commonly used terms focused on the perceived source of threat, general terms for difficulty, or clinical language, typically variants of "paranoia or anxiety.". - Of five selected terms, participants were more likely to report that "anxiety" aligned with their experience, followed by "suspiciousness.". Abstract: While recent studies have prompted re-evaluation of the term "schizophrenia, " few have examined the use of terms to describe persecutory ideation (PI) or paranoia. This study examines the preferences and terms used by a cross-diagnostic population of individuals ( N = 184) with lived experience using an online survey. Participants most commonly described their PI in terms of the perceived source of threat, followed by clinical language, most commonly variants of "paranoia" and "anxiety." Of five selected terms assessed quantitatively – "anxiety, " "paranoia, " "persecutory thoughts, " "suspiciousness, " and "threat thoughts" – participants were more likely to report that "anxiety" aligned with their experience of PI, followed by "suspiciousness." Endorsement of terms more specific to PI was associated with self-report PI severity, while a preference for "anxiety" over other terms was both associated with less severe PI and lower scores on a measure of stigma. These results suggest that the heterogeneity of terms used by individuals with lived experience support a person-centered approach to language describing such experiences.